Determination Of Exchangeability Cations (Ec), Texture And C-Organic Content In Mineral Soils and Peat - Ahmad Gazali Aros Ai; Vera Lorensya Br. Sembiring; Astri Mutiara Dewi; Anggi Putri Rahayu; Rahmi Rahmi; Lenny Marlinda (ALKIMIA, 2022)
EC or can be called exchangeable cation is a nutrient cation found in the soil. This is useful for indicating the degree of alkaline saturation, which indicates that the more saturated the soil base, the more fertile the soil will be. This study aims to obtain supporting information to obtain soil conditions that show the quality of the land as a growing medium. The method used for texture analysis on this soil refers to SNI 3423.03:1994 and C-Organic content analysis refers to SNI 4720.13:1998. The cation level test was carried out using NH4OAc solution with a Microwave Plasma Atomic Emission Spectroscopy (MP-AES) instrument. This instrument has a principle, namely atomic emission which is a form of energy produced by an atom when it returns to the ground state (Ground State) of the excited state (Excitation State). The results of this cation level test with analyte concentrations of K, Ca, Na and Mg with sample code SJ2022-01826 successively 0.65; 3,59; 0.82 and 0.94. The amount of cation content in fertile soil is worth at least 6 mg / L in accordance with the provisions of the Chemical Technical Manual.